Ultrafast (picosecond) laser oscillator for educational use - Pflaum, Christoph; Alexeev, Ilya; Ugurlu, Asli Dilara; Seerdar, G (European Journal of Physics, 2016)
Here, we present a description of an inexpensive ultrafast self-starting passively mode-locked laser oscillator that can be constructed using widely available off-the-shelf optical components. Such a laser system can be used to teach students the principles of solid state laser engineering, demonstrate a number of nonlinear optical phenomena, and perform qualitative and quantitative comparisons between numerical laser modeling and experimental results.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.c3sim.ultraf
Keywords: passive mode-locking; semiconductor saturable absorber; ultrafast laser